Biomechanical analysis of jumping back kick of elite taekwondo athletes - Qian, J.; Fu, C.; Fang, Y.; Li, Q. (International Journal of Sports Science and Engineering, 2010)
The article analyzes the motion of jumping back kicks by studying four elite athletes of the Chinese national team employing biomechanical three-dimensional DTL method. The jumping back kick is divided into 5 stages and three different movement phases according to time sequence. Combining all stages of body joint angles, velocity and other technical parameters and mechanical theory, the results show as following: The time of run-up stage should be shortened and the knee bending angle should be small. During right foot buffering phase, the right ankle, knee and hip bend in correct order rapidly and the gravity gets lost; swing the arms downward rapidly to increase extension and gravity; tread the land swiftly and strongly and stretching the hip and knee upward with violent force to increase the momentum on the ground and obtain greater reaction and greater initial speed and raise vertical height; make sure to swing the left foot with upper body backward and control the center of gravity well; twist the waist to press the left leg down and keep the right toe hooked tightly to the leg tightly; fold the arms sideward and fix the head to help the body the body swivel; unfold the left arm when the right leg is to tread the ground. In the phase of decline, keep the head down in chest with a view of self-protection; decrease the momentum of outreach through the internal muscular strength. The analysis is expected to provide a helpful reference for the technical teaching and innovation of Taekwondo.